I am Malala : how one girl stood up for education and changed the world - Yousafzai, Malala, 1997- (Little, Brown and Company, 2015)
Describes the life of the young Pakistani student who advocated for women's rights and education in the Taliban-controlled Swat Valley, survived an assassination attempt, and became the youngest nominee for the Nobel Peace Prize.